Digital Literacy Education to Increase Sukuk Investment in Indonesia - Zaky Muhamad Hikam; Ach. Badrus Soleh; Fahrudin Rasta Hidayat (FEBI UIN Sunan Kalijaga Yogyakarta, 2023)
The practice of investing in the Islamic economy is well known, because the practice of Islamic investment starts from the Arabian Peninsula. In practice, investments are made not in the form of debt, but in the form of sharing profits and risks which are transformed into business partnerships called musyarakah, mudharabah in trade or business. One form of sharia investment, namely sukuk. In order to increase the application of sukuk in Indonesia, digital literacy education is becoming increasingly important. The implementation of digital education is carried out through the Instagram application, namely by posting posters containing the meaning of sukuk, types of sukuk, characteristics of sukuk, types of sukuk issued in Indonesia, benefits of sukuk, and benefits of investing in sukuk, and users can Discuss via comments. In the comments column there are 3 questioners. And with the implementation of this activity, it can increase the public's willingness to invest in sukuk or sharia bonds.